2011
DOI: 10.1021/nl200824p
|View full text |Cite
|
Sign up to set email alerts
|

Octopods versus Concave Nanocrystals: Control of Morphology by Manipulating the Kinetics of Seeded Growth via Co-Reduction

Abstract: Au/Pd octopods and concave core@shell Au@Pd nanocrystals have been prepared by coupling for the first time a seed-mediated synthetic method with co-reduction. The integration of these two methods is central to the formation of these binary Au/Pd nanocrystals wherein the kinetics of seeded growth are manipulated via the co-reduction technique to control the final morphology of the nanocrystals. Significantly, the synthesis of these structures under similar reaction conditions illustrates that they are structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
176
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(187 citation statements)
references
References 46 publications
(64 reference statements)
7
176
0
4
Order By: Relevance
“…This is quite different from Au−Pd nanostructures synthesized by seed-mediated nucleation and growth where gold NC core is preformed and then followed by The Journal of Physical Chemistry C the reduction of Pd precursor 46 or coreduction of Au and Pd precursors. 50,51 Electrocatalytic Activity for Methanol Oxidation. It has been reported that Pd-based NCs have a high electrocatalytic activity toward ethanol or methanol oxidation in alkaline solutions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is quite different from Au−Pd nanostructures synthesized by seed-mediated nucleation and growth where gold NC core is preformed and then followed by The Journal of Physical Chemistry C the reduction of Pd precursor 46 or coreduction of Au and Pd precursors. 50,51 Electrocatalytic Activity for Methanol Oxidation. It has been reported that Pd-based NCs have a high electrocatalytic activity toward ethanol or methanol oxidation in alkaline solutions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Integrating different metallic NCs into a HMNC can introduce new and enhanced properties, or multi-functionality not found in the parent metal NCs [1][2][3][4][5][6][7] . The properties of a HMNC are clearly architecture dependent [7][8][9][10][11][12][13][14][15][16][17] . Therefore, architectural engineering of HMNCs can significantly increase the possibilities to create new and more varied properties for application explorations.…”
Section: Spatial Arrangement Edge Satellitementioning
confidence: 99%
“…The shape of the satellite NCs can be varied by the [Ag þ ]/[Pd 2 þ ] concentration ratio and the concentration of HCl (which is used as an additive). These preparation variables are able to modify the preferred growth directions of the metal atoms 33 or the reduction rates of their precursors 10,34 to yield different shapes of satellite NCs.…”
Section: Principlesmentioning
confidence: 99%
“…[21][22][23][24][25] Perhaps most remarkable of all is the level of control that has been attained over the synthesis of nonconvex, irregular, and even punctured particles. Branched colloids and nanocrystals, such as octapods [26][27][28][29][30] and tetrapods, 31,32 have been created, as well as other nonconvex shapes, e.g., nanostars 15,[33][34][35] and colloidal caps. [36][37][38] Moreover, there is a better understanding of the way to achieve phase behaviour that is dominated by entropic contributions in experimental systems.…”
Section: Introductionmentioning
confidence: 99%